Association of circulating metabolites and polygenic risk score with incident type 2 diabetes: a prospective community-based cohort study - Masato Takase; Naoki Nakaya; Mana Kogure; Rieko Hatanaka; Kumi Nakaya; Ippei Chiba; Sayuri Tokioka; Kotaro Nochioka; Tomohiro Nakamura; Naho Tsuchiya; Takumi Hirata; Seizo Koshiba; et al. (Cardiovascular Diabetology)
Abstract Background No previous studies have explored metabolites associated with both genetic predispositions to type 2 diabetes (T2DM) and T2DM onset. Therefore, we aimed to explore metabolic profiles using genetic risk to identify pathways for tailored T2DM prevention strategies. Methods This prospective community-based cohort study in Japan included a total of 12,461 participants aged ≥ 20 years. Genetic predictors were genome-wide and pathway-based polygenic risk scores (PRSs). We quantified 43 metabolites using nuclear magnetic resonance spectroscopy. T2DM was defined as a non-fasting glucose level of ≥ 200 mg/dL, glycated hemoglobin level ≥ 6.5%, or self-reported T2DM treatment. A modified Poisson regression model was used to examine the associations of PRSs and metabolites with T2DM incidence. Linear associations were tested using the restricted cubic spline, and mediation analysis was conducted to assess the mediating effect of metabolites on the association between PRSs and T2DM incidence. Results During the 4.3-year median follow-up period, 354 T2DM cases were identified. A higher PRS was associated with incident T2DM (relative risk [RR] 2.09, 95% confidence interval [CI], 1.68–2.60, P < 0.001, 1-standard deviation [SD] increment). The nitrogen compound transport pathway PRS was associated with incident T2DM (RR 1.32, 95% CI 1.03–1.70, P < 0.001, 1-SD increment). Fourteen metabolites like glucose, 2-ketoisocaproic acid, glutamic acid, leucine, 2-aminobutyric acid, 2-hydroxybutyric acid, valine, 3-methyl-2-oxobutyric acid, alanine, 3-hydroxybutyric acid, 3-methyl-2-oxiovaleric acid, formic acid, arginine, and tyrosine were positively associated with the risk of T2DM. Only glycine was inversely associated with the risk of T2DM. Among 43 metabolites, 14 metabolites were positively associated with PRS (P for linear trend < 0.05). 3-hydroxyisobutyric-acid, 2-Aminobutyric acid, 2-ketoisocaproic acid, 2-hydroxybutyric acid, leucine, glycine, and glucose mediated the association between PRS and incident T2DM. Conclusions Several metabolites were found to mediate the association between PRS and incident T2DM. These findings may contribute to a better understanding of the metabolic pathways involved in genetic susceptibility to T2DM.